The Characteristic of Mothers of Children Under Five in Integrated Health Care Service Activities in Tarus Community Health Center - Teodora Selvia Longa; Marylin Susanti Junias; Indriati A. Tedju Hinga (Yayasan Literasi Sains Indonesia, 2023)
Integrated service postis is a basic health activity organized from, by, and for the community to reduce infant mortality, and maternal mortality (pregnancy, childbirth, and postpartum), cultivate small happy, and prosperous families, and increase the role of participants and the community's ability to develop health and welfare activities and family planning. This study aims to describe the characteristics of mothers under five in integrated service posts in the working area of ​​the Tarus Health Center in 2022. The type of research is a descriptive study using a cross-sectional research design. The population in this study were all mothers of children under five who were recorded at integrated service posts in the working area of ​​the Tarus Health Center who had toddlers from 0-60 months of age as many as 3,675 people and the sampling technique used purposive sampling with a sample of 97 people. The results showed that the distribution of respondents was based on the number of visits to the integrated service post, namely active visits (52.5%), and inactive visits (47.4%). The age of the mother of children under five is at most 31-35 (36.1%), the mother's education is high school education at most (41.2%), the mother's occupation is the most in IRT work (51.5%), Mother's reassurance toddlers who have good knowledge are (59.8%), less well are as many as (40.2%), the distance from house to integrated service post is near (54.6%), far away (45.3%). Suggestions for community health service centers can provide understanding and awareness to mothers of toddlers so that they routinely bring children under five to the integrated service post every month so that the growth and development of toddlers can be monitored.